2021
DOI: 10.3389/fpsyg.2021.701134
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Authentic Sports Leadership Program for Coach

Abstract: Purpose: This paper studies the effects of authentic sports leadership training on coaches' self-perception of their own authentic leadership, perceived justice, competence, overall self-efficacy, and collective efficacy. Additionally, players' perceptions of their coaches with respect to their authentic leadership, perceived justice, competence, collective efficacy, satisfaction with the coach, and support for basic psychological needs were analyzed.Design: Twenty-five football and handball coaches were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The results achieved in this research coincide with another where the perception of authentic leadership increased, but greater athlete satisfaction with their coach was not achieved. 36 In contrast, some results directly relate authentic leadership with athlete satisfaction and greater confidence in the coach. 37 Therefore, it is possible to indicate that perceived justice is a variable with complementary and necessary characteristics for developing authentic leadership to modulate coaching satisfaction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results achieved in this research coincide with another where the perception of authentic leadership increased, but greater athlete satisfaction with their coach was not achieved. 36 In contrast, some results directly relate authentic leadership with athlete satisfaction and greater confidence in the coach. 37 Therefore, it is possible to indicate that perceived justice is a variable with complementary and necessary characteristics for developing authentic leadership to modulate coaching satisfaction.…”
Section: Discussionmentioning
confidence: 98%
“…26 Based on the above, Malloy and Kavussanu, 35 in an intervention designed to increase authentic coach leadership, evidenced athletes' greater enjoyment and prosocial behavior. In this sense, Soto et al 36 showed that athletes perceived that their coaches were more competent when they developed greater abilities related to authentic leadership. Likewise, Bandura and Kavussanu 37 concluded that authentic leadership perceived by athletes is related to satisfaction, commitment, and enjoyment.…”
Section: Perceived Authentic Leadership and Justice As Mediating Vari...mentioning
confidence: 99%
“…Thus, the explanation of the relationship between authentic leadership and athletes' positive perception of BPN support may be based on internal interpersonal characteristics in the conceptualization of authentic leadership (Bandura & Kavussanu, 2018;Soto Garcia et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the middle of the space between these two variables, many other factors affect coach-athlete interaction, as well as sport performance and athlete satisfaction. In response, some authors have investigated the role of psychosocial elements such as leadership or fairness in athletes' perceptions of coaches (Bosselut et al, 2012;De Backer et al, 2011;Leo et al, 2019;Pires et al, 2022;Soto-Garcia et al, 2021, 2023. Leadership in sport is described as a process which the coach, manager or even the same athletes can influence the motivation and behavior of the others (athletes/teammates) to look for and work for achieve a common goal (Turnnidge & Côté, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation